The Dynamics of Psychological Reactance in Society Towards Physical Distancing Policy - Huda, Rifa’i Anas Amirul; Rahmawati, Intan (Journal of Health and Behavioral Science, 2023)
In the July 2021 period, Covid-19 cases in Indonesia jumped sharply. The Indonesian government responded to the spike in cases by implementing a physical distancing policy called PPKM (Pemberlakuan Pembatasan Kegiatan Masyarakat). One of the public's responses to the policy is reluctance or disobedience to existing policies because they experience psychological reactance. This research was conducted with the aim of understanding the dynamics of community psychological reactance related to the physical distancing policy in Indonesia. The study used a qualitative method with a phenomenological approach and analyzed using Miles and Huberman's thematic analysis. Sampling was done by using homogeneous variance purposive sampling technique. Collecting data used in this study is to conduct interviews. Research informants totaled 3 people. This study resulted that the three informants felt that their activities were limited during the implementation of the Physical distancing policy. The existence of the physical distancing policy also caused the three informants to feel threatened, both directly and indirectly in economic and academic terms, and their freedoms were disturbed. The form of reactance experienced by each informant was disappointment with the government. The responses of the three informants in an effort to restore their freedom include; not obeying the PPKM rules and breaking them by staying together with the crowd.